Repenser le rôle des victimes dans la justice transitionnelle en Tunisie : le cas de la « Journée de la loyauté » - Sélima Kebaili (L’Année du Maghreb)
In Tunisia, a transitional justice process has been initiated in 2011 and materialized by the creation of a Truth commission (2011-2018) in a context of strong political cleavage between political parties and groups of the civil society. This article focuses on how victims’ associations have invested this process and its different forms of politicization. It is based on the analysis of the mobilization of an association of female victims and shows how, through the organization of a conference in the mode of truth commissions, the organization influenced the transitional justice process from the first stages of its implementation in 2011. Based on interviews conducted between 2015 and 2018 with members of the association and an analysis of the archives produced by the latter, the article studies the construction of the figure of the female victim, shows how the testimonies of the victims were key elements of their contribution to the implementation of the process, and highlights the effects of these narratives on the formal mechanisms of Tunisian transitional justice. The article thus shows that the figure of the female victim is constructed by activists who appropriate the label of transitional justice in negotiations with actors of the formal political sphere.